Snow depth, sea ice thickness and interface temperatures derived from measurements of SIMBA buoy 2020T60 - Preußer, Andreas; Nicolaus, Marcel; Hoppmann, Mario (In: Preußer, A et al. (2025): Snow depth, sea ice thickness and interface temperatures derived from measurements of SIMBA buoys deployed in the Arctic Ocean and Southern Ocean between 2012 and 2023 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.973193, 2025)
The Snow and Ice Mass Balance Array (SIMBA) is a thermistor string type IMB (Jackson et al., 2013) which measures the environmental temperature SIMBA-ET and a temperature change around the thermistors after a weak heating is applied to each sensor (SIMBA-HT). SIMBA 2020T60 (a.k.a. simba_havoc0101) is an autonomous instrument that was installed on drifting sea ice in the Central Arctic Ocean (Polarstern PS122 (MOSAiC) in 2019/20) as part of the project HAVOC. Its thermistor chain is 10 m long, and equipped with 251 thermistors (Maxim Integrated DS28EA00) at a spacing of 4 cm. Based on a manual classification method, the SIMBA-ET and SIMBA-HT were processed to obtain snow depth and ice thickness (smoothed with a 3-day running mean), as well as the thermistor number, the vertical position Z relative to the snow-ice interface and the measured SIMBA-ET at each detected interface (atmosphere-snow, snow-ice and ice-ocean) for the period between 2020-01-08T09:00:17 and 2020-04-20T21:00:16. To do this, we combined two derivatives of measured temperatures (the ET vertical gradient and HT rise ratio) to reduce the detection uncertainty of all interfaces considered. The snow or ice surface, consequentially the snow depth, is determined by the ET vertical gradient. Potential formation of snow ice is not explicitly considered in this data set, but may occur as depicted by vertical changes of the snow-ice interface position. The ice-ocean interface is usually determined using the HT rise ratio and serves as the lower limit for ice thickness. Overall, the accumulated error is 2 to 4 times the sensor spacing for both the snow depth and ice thickness. For interface temperatures, individual sensors in the chain measure with a temperature resolution of 0.0625°C, with the overall accuracy landing in the range of ± 2°C (Jackson et al., 2013). After the snow cover has melted, negative values for snow depth may indicate the onset of ice surface melt.
Keywords: Arctic PASSION; Autonomous buoy; Ice mass balance; Sea ice interfaces; Sea ice thickness; snow depth; Temperature thermistor